Memanfaatkan Pekarangan Kampus untuk Lahan Sayuran sebagai Upaya Meningkatkan Kemampuan Wirausaha Mahasiswa STT Sabda Agung (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The objective of this activity is to foster a spirit of entrepreneurship among students by utilizing productive land on the STT Sabda Agung campus as an educational vegetable garden. This activity is designed to engage students actively and collaboratively throughout the entire agricultural cycle, from the planning stage, land preparation, planting various types of vegetables such as water spinach, mustard greens, and spinach, maintenance, to the harvesting and marketing of the produce. The primary focus of this activity is not only on the technical aspects of farming but also on character development, fostering independence, and enhancing students’ managerial skills in managing small-scale business units. The outcomes of this initiative demonstrate a significant increase in students’ interest and understanding of agriculture-based entrepreneurship, particularly regarding the utilization of backyard spaces. In addition to providing educational value, this land optimization has successfully transformed the campus area into a productive and aesthetically pleasing green space. As a result, students now possess practical skills that can serve as a foundation for future economic independence, particularly in the service sector. Through this integration of theory and practice, it is hoped that an innovative learning ecosystem will be created to foster the emergence of competent young entrepreneurs who are environmentally conscious.